Explaining Benefit Take-up Behavior – The Role of Financial Incentives - Olof Rosenqvist; Håkan Selin (CESifo GmbH, 2024)
Take-up of social benefits is a central issue in poverty alleviation and fiscal evaluations of policy reforms. However, it is difficult to find exogenous variation in the benefit level, and little is therefore known about take-up responses to basic financial incentives. We exploit large and plausibly random variation in levels of "flat-rate parental leave benefits", which all Swedish parents are entitled to. There are no financial reasons to leave money on the table, but take-up is nevertheless imperfect. Higher benefits substantially increase claiming across the income distribution. We further detect sizable spillover effects on subsequent take-up of low-income earners.
Keywords: H24; J22; 330; parental benefits; incomplete take-up; after-tax benefits